Migraine and the risk of cardiovascular and cerebrovascular events: a meta-analysis of 16 cohort studies including 1 152 407 subjects. Issue 3 (27th March 2018) - Mahmoud, Ahmed N; Mentias, Amgad; Elgendy, Akram Y; Qazi, Abdul; Barakat, Amr F; Saad, Marwan; Mohsen, Ala; Abuzaid, Ahmed; Mansoor, Hend; Mojadidi, Mohammad K; Elgendy, Islam Y
Abstract : Objectives: To perform an updated meta-analysis to evaluate the long-term cardiovascular and cerebrovascular outcomes among migraineurs. Setting: A meta-analysis of cohort studies performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources: The MEDLINE, Web of Science and Cochrane Central Register of Controlled Trials databases were searched for relevant articles. Participants: A total of 16 cohort studies (18 study records) with 394 942 migraineurs and 757 465 non-migraineurs were analysed. Primary and secondary outcome measures: Major adverse cardiovascular and cerebrovascular events (MACCE), stroke (ie, ischaemic, haemorrhagic or non-specified), myocardial infarction (MI) and all-cause mortality. The outcomes were reported at the longest available follow-up. Data analysis: Summary-adjusted hazard ratios (HR) were calculated by random-effects Der-Simonian and Liard model. The risk of bias was assessed by the Newcastle-Ottawa Scale. Results: Migraine was associated with a higher risk of MACCE (adjusted HR 1.42, 95% confidence interval [CI] 1.26 to 1.60, P<0.001, I 2 =40%) driven by a higher risk of stroke (adjusted HR 1.41, 95% CI 1.25 to 1.61, P<0.001, I 2 =72%) and MI (adjusted HR 1.23, 95% CI 1.03 to 1.43, P=0.006, I 2 =59%). There was no difference in the risk of all-cause mortality (adjusted HR 0.93, 95% CI 0.78 to 1.10, P=0.38, I 2 =91%), with a considerable degree of statistical heterogeneity between the studies. The presence of aura was an effect modifier for stroke (adjusted HR aura 1.56, 95% CI 1.30 to 1.87 vs adjusted HR no aura 1.11, 95% CI 0.94 to 1.31, P interaction =0.01) and all-cause mortality (adjusted HR aura 1.20, 95% CI 1.12 to 1.30 vs adjusted HR no aura 0.96, 95% CI 0.86 to 1.07, Pinteraction <0.001). Conclusion: Migraine headache was associated with an increased long-term risk of cardiovascular and cerebrovascular events. This effect was due to an increased risk of stroke (both ischaemic and haemorrhagic) and MI. There was a moderate to severe degree of heterogeneity for the outcomes, which was partly explained by the presence of aura. PROSPERO registration number: CRD42016052460 .